Funding Shocks and Credit Quality - Enrico C. Perotti; Magdalena Rola-Janicka (Tinbergen Institute, 2019)
Some credit booms, though by no means all, result in financial crises. While risk-taking incentives seem a plausible cause, market participants do not appear to anticipate increasing risk. We show how credit expansions driven by credit supply shocks may be misunderstood as productivity driven, due to the opacity of bank balance sheets. Large funding shocks may induce some intermediaries to scale up speculative lending, distorting price signals. Other banks and firms may misjudge actual profitability, reinforcing the credit expansion. Similarly, at times of low saving supply credit may be inefficiently low, and speculative assets underpriced.
Keywords: 330